ENHANCING LEFT DORSOLATERAL PREFRONTAL CORTEX ACTIVITY THROUGH TDCS COMBINED WITH NEUROFUNCTIONAL TRAINING IN CHILDREN WITH ASD: A RANDOMIZED, DOUBLE-BLIND, CONTROLLED CLINICAL TRIAL (CIPEEX, 2025)
Introduction: Autism spectrum disorder (ASD) frequently involves motor impairments that affect mobility and balance. Transcranial direct current stimulation (tDCS) may potentiate gains from motor training. Objective: To compare the effects of 10 sessions of neurofunctional training combined with active anodal tDCS over the left dorsolateral prefrontal cortex (lDLPFC) versus sham tDCS on functional mobility, spatiotemporal gait parameters, and functional balance in children with ASD. Methods: Randomized, double-blind, placebo-controlled clinical trial including 24 children. The intervention comprised two weeks of neurofunctional training (treadmill walking plus a postural-control circuit) combined with active lDLPFC tDCS (1 mA) or sham. Participants were assessed pre-intervention, post-intervention, and at follow-up using the Timed Up and Go (TUG), the 10-Meter Walk Test (10MWT), and the Pediatric Balance Scale (PBS). Results: On the TUG, a follow-up effect was observed, with shorter execution time in the active tDCS group versus control (mean difference [MD] = −4.023 s; 95% CI: −6.753 to −1.292 s; p=0.002; d=1.5). On the PBS, the active tDCS group showed higher scores post-intervention (MD=6.417; 95% CI: −0.4385 to 13.27; p=0.049; d=1.0) and at follow-up (MD=7.417; 95% CI: 0.9484 to 13.88; p=0.023; d=1.2). Spatiotemporal gait parameters did not differ between groups (p>0.05). Conclusion: Anodal tDCS over the lDLPFC combined with neurofunctional training is safe and yields clinically meaningful improvements in balance and functional mobility—with 30-day retention—in children with ASD, without detectable effects on spatiotemporal gait variables under the tested conditions.
Keywords: Autism Spectrum Disorder; Gait; Balance; Child; Transcranial Direct Current Stimulation